Tinjauan Siyasah Dusturiyah terhadap Sistem Proporsional Terbuka: Studi Analisis UU Nomor 7 Tahun 2017 tentang Pemilihan Umum - Dimas Amanda Pebri Saputra; Agustina Nurhayati; Muhammad Irfan (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This normative study analyzes the open proportional system based on Law Number 7 of 2017 and PKPU Number 10 of 2023 from the perspective of siyasah dusturiyah. Although it supports the Islamic principles of deliberation and voter sovereignty, this system gives rise to issues such as high political costs, money politics, and polarization. The findings indicate the need to strengthen the authority of political parties and revise regulations by the House of Representatives (DPR) in order to minimize oligarchic practices. The General Election Commission (KPU) is also encouraged to be more selective in aligning its regulations with Constitutional Court decisions. In terms of implications, this study enriches the contemporary Islamic legal literature based on maqasid al-shariah in order to realize governance with a strong system of checks and balances.